Harnessing Alternative Technology for the Sustainability of Biodiesel Production - E. J. Eterigho; T. S. Farrow; D. O. Agbajelola; S. E. Ejejigbe; A. P. Harvey (Iranica Journal of Energy and Environment, 2016)
Biofuel, a renewable energy is mainly produced by transesterification of fatty acids either in presence of enzyme or catalysts. The transesterification relies on the use of either strong base or strong acid homogeneous catalysts for effective performance; but, homogeneous catalysts are associated with a variety of technical hurdles that limit their use for biodiesel production. Although there have been recent developments in heterogeneous catalysts for biodiesel production via transesterification; the separation of methyl ester (FAMEs) from crude glycerol and alcohol recovery are still major hindrances. A possible alternative could be the use of solid acid catalysts in thermocatalytic cracking of triglycerides. Sulphated zirconia catalyst was evaluated for thermocatalytic cracking of triglycerides at a relatively low temperature (270oC) and atmospheric pressure. The catalyst was found to be active toward cracking vegetable oils to methyl esters. The catalyst at this temperature exhibited different selectivity towards formation of saturated and unsaturated methyl esters. The catalyst yield of methyl esters under these conditions was 58% while 80% of the product being unsaturated. This opens up the possibility of controlling the degree of saturation of the methyl ester product by catalyst choice, to produce more or less saturated fuels for different markets. The range of products from gases to middle distillates and the unique selectivity for saturated and unsaturated esters may be a significant process advantage  of  this form  of  catalytic  cracking.  An  important  long  chain  unsaturated  alcohol  (1- Heptatriacotanol) was also identified. The unsaturated alcohol is known as an industrial chemical.